Embracing the Transformation of Indonesian SMEs in the Era of Creative Destruction - Asmar, Asmar; Baharuddin, Aris; Kasmita, Maya (Universitas Negeri Makassar, 2024)
Small and Medium Enterprises (SMEs) are the cornerstone of Indonesia’s economy, significantly contributing to national economic output and employment. However, the rapid pace of technological advancement has introduced the phenomenon of creative destruction, where traditional business models are replaced by innovative ones, posing significant challenges for SMEs. This study explores how Indonesian SMEs can adapt to creative destruction by leveraging innovation and strategic planning. Using a qualitative approach, data were collected through interviews with SME owners, policymakers, and industry experts, complemented by secondary data from government and international reports. The findings reveal that while SMEs face barriers such as limited technology access, inadequate digital literacy, and financial constraints, proactive strategies—such as forming partnerships, adopting digital tools, and innovating business models—enable adaptation. Nonetheless, a lack of long-term planning and strategic foresight undermines sustainability. The research underscores the importance of a multi-stakeholder approach involving government, private sector, and educational institutions to provide tailored support, enhance digital literacy, and streamline policy implementation. This study contributes to the theoretical discourse by applying Schumpeter’s theory of creative destruction and Rogers’ Diffusion of Innovation framework to the Indonesian SME context. Practical implications include fostering collaboration, promoting digital adoption, and addressing systemic barriers to ensure SMEs thrive amidst disruption. Future research is recommended to explore longitudinal studies on innovation sustainability, sectoral comparisons, and the role of external stakeholders in supporting SME transformation. By addressing these challenges, SMEs can seize opportunities to drive economic growth and resilience in Indonesia.